A influência da governança corporativa na divulgação socioambiental de empresas listadas na B3. - Bárbara Siqueira da Silva (2020)
Corporate governance is a set of rules and recommendations that aim to ensure the institution's transparency and integrity. Thus, those responsible for management seek to carry out Corporate Social Responsibility (CSR) practices, as well as publicize them so that the company is perceived by the stakeholders as being legitimate, thus avoiding threats to reputation, and, consequently, the loss of legitimacy. After all, if the company is not seen as operating within what is socially accepted, it can run serious risks of continuity. Thus, the sustainability report is the document that informs stakeholders about the mechanisms and actions that companies have been adopting to improve the environment in which they operate. However, this disclosure is voluntary. In light of this, the research has the general objective of identifying which characteristics of corporate governance, of companies in Brazil, Bolsa, Balção (B3), influenced the dissemination of socio-environmental information, in the period from 2013 to 2018. Regarding the procedures used, the research is documentary, since it uses content analysis, sustainability reports, to measure the level of socio-environmental disclosure, in addition to capturing the corporate governance variables of the reference forms. As for the approach to the problem, the research is quantitative, as it uses factor analysis to verify the factors of socio-environmental disclosure, in addition to logistic regression to verify the likelihood of companies publishing the sustainability report and multiple linear regression to verify the level of disclosure given corporate governance characteristics. The results of the logistic regression show that the Size of the Board of Directors (TCA), the Independence of the Board (IC), the Pollution Potential and the Use of Natural Resources (PPURN) and the Size of the Company (TAM) have a positive relationship and significant with the likelihood of the company publishing the sustainability report. In relation to multiple linear regression, the variables Capital Concentration (CC), Level of Governance (NG), PPURN and TAM showed a positive and significant relationship with the level of socio-environmental disclosure. Therefore, the result contributes to the literature, as it indicates that the adherence to the sustainability report is linked to the members that make up the board of directors, who have the power to make decisions. The levels of socio-environmental information disclosed in these documents are related to the level of governance, in a broader way, as well as to the concentration of capital. The size of the company and PPURN affect both the likelihood of adhering to the sustainability report and the amount of information disclosed. Thus, the study demonstrates that the disclosure of socio-environmental information can be seen from two perspectives: the first refers to the decision to adhere to the sustainability report, which is linked to the composition of the board of directors; the second is related to the content that is disclosed in this document, which is influenced by broader issues related to corporate governance, such as the level of listing on the stock exchange and the concentration of capital. Despite this differentiation, the size of the company and the activity performed is a common point, which influences both the decision to prepare the report and the content disclosed.